2019
DOI: 10.2196/15062
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Use of a Mobile Health Strategy App and Biological Changes in Breast Cancer Survivors: Prospective Pre-Post Study

Abstract: Background There is a bidirectional relationship between chronic low-grade inflammation and cancer. Inflammatory markers, such as interleukin-6 (IL-6), have been associated with both the malignant transformation of epithelial cells and tumor progression, thus linking low-grade inflammation with a higher risk of cancer and recurrence in the survival phase. Therefore, they are considered valuable prognostic biomarkers. Knowing and finding appropriate primary prevention strategies to modify these para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…These studies can be found in Table 2 . Each app had different features, including digital diaries [ 7 , 44 - 49 ], coach feedback [ 7 , 44 - 47 , 49 - 51 ], personalized physical exercise programs and nutrition plans [ 49 , 50 ], general nutrition and physical exercise guidelines [ 45 , 51 ], psychological support courses [ 45 , 51 ], a secure message portal to their health care teams [ 7 , 48 ], health knowledge education [ 46 , 48 , 51 ], and daily tasks [ 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies can be found in Table 2 . Each app had different features, including digital diaries [ 7 , 44 - 49 ], coach feedback [ 7 , 44 - 47 , 49 - 51 ], personalized physical exercise programs and nutrition plans [ 49 , 50 ], general nutrition and physical exercise guidelines [ 45 , 51 ], psychological support courses [ 45 , 51 ], a secure message portal to their health care teams [ 7 , 48 ], health knowledge education [ 46 , 48 , 51 ], and daily tasks [ 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some thoughts on reconstruction strategies in the implementation of public English ecological classrooms in the context of "Internet +" are mentioned in the literature [21]. [22] According to previous research on public English ecological classrooms under the background of "Internet plus," "attention used to focus on individual students' experiences and school achievements, but now it has turned to a series of factors that constitute the reconstruction strategy of students' public English ecological classroom" [23]. According to research, the public English ecological classroom should be investigated in the context of the current environment and a development reconstruction strategy that pays attention to the world, especially in light of "Internet plus."…”
Section: Related Workmentioning
confidence: 99%
“…text messages [16,23,74], wearable devices [29,83], and mobile apps [14,27,41,84,85], as forms of delivery. Recent studies have also begun to integrate mHealth interventions with gamification [72,86] and other smartphone features like location sensing [87], thereby providing deeper insights into how these interventions influence participants.…”
Section: For Example Mhealth Interventions For Cancer Have Predominan...mentioning
confidence: 99%